1997
DOI: 10.1523/jneurosci.17-04-01493.1997
|View full text |Cite
|
Sign up to set email alerts
|

Experience-Dependent Developmental Plasticity in the Optic Lobe ofDrosophila melanogaster

Abstract: Early experience can affect nervous system development in both vertebrate and invertebrate animals. We have now demonstrated that visual stimulation modifies the size of the optic lobes in the laboratory fruitfly Drosophila melanogaster. Monocular deprivation (painting over one eye) decreases the aggregate volume of the lamina, medulla, and lobula plate by up to 6%. The laminae of control flies kept in complete darkness showed a more robust volume difference that could be as much as 30%. An electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
134
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(143 citation statements)
references
References 48 publications
6
134
3
Order By: Relevance
“…The experience-dependent developmental mechanisms have been clearly demonstrated for the visual, auditory, somatosensory and motor systems in virtually all species, from humans to Drosophila (Barth et al 1997, Berardi et al 2000. Childhood sensory deprivation, such as monocular deprivation (Doupe and Kuhl 1999, Fagiolini et al 1994, Harwerth et al 1986, Huang et al 1999, Issa et al 1999, Olson and Freeman 1980 or monaural plugging (Knudsen et al 1984) and alterations in sensory input, such as caused by strabismus (Berman and Murphy 1981), rearing in a restricted auditory environment, or misalignment of the auditory and visual space maps (Brainard and Knudsen 1998, King and Moore 1991), result in lifelong changes of neural networks and a deficit in the corresponding function.…”
Section: Ontogenetic Acquisition Of Synchronous Frontoposterior Connementioning
confidence: 99%
“…The experience-dependent developmental mechanisms have been clearly demonstrated for the visual, auditory, somatosensory and motor systems in virtually all species, from humans to Drosophila (Barth et al 1997, Berardi et al 2000. Childhood sensory deprivation, such as monocular deprivation (Doupe and Kuhl 1999, Fagiolini et al 1994, Harwerth et al 1986, Huang et al 1999, Issa et al 1999, Olson and Freeman 1980 or monaural plugging (Knudsen et al 1984) and alterations in sensory input, such as caused by strabismus (Berman and Murphy 1981), rearing in a restricted auditory environment, or misalignment of the auditory and visual space maps (Brainard and Knudsen 1998, King and Moore 1991), result in lifelong changes of neural networks and a deficit in the corresponding function.…”
Section: Ontogenetic Acquisition Of Synchronous Frontoposterior Connementioning
confidence: 99%
“…Flies kept in complete darkness were found to develop a first visual neuropil (lamina) reduced in volume by up to 30% compared with flies raised under normal light conditions. These marked differences were attributed to the absence of a lightdependent size increase of the photoreceptor terminals which, under normal light conditions, is induced in animals within a critical period which is maximal during about the first 12 h of the fly's adult life (Barth et al, 1997). Electron-microscopic studies have also shown the synaptogenesis of the connections between the photoreceptor cells and their follower neurons (large monopolar cells: LMCs) in the lamina to be affected by light reversals, reducing the synaptic density in light-reared flies subject to dark exposure (Rybak & Meinertzhagen, 1997).…”
Section: Experience-dependent Development Of the Fly Visual Systemmentioning
confidence: 99%
“…It has been shown that during a critical period of 12 h after the flies' hatching from pupae, light experience is essential for the neuropils to develop a normal volume. When kept in the dark, the visual neuropils were smaller (Barth et al, 1997). Part of these effects could be attributed to the light-dependent synaptogenesis between photoreceptor cells of the retina and cells of the lamina, the fly's first visual neuropil (Barth et al, 1997;Rybak & Meinertzhagen, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the expression of the visual protein opsin in the bluefin killifish varies with rearing light spectrum (Fuller et al, 2005). In Drosophila melanogaster, the development of the optic lobes and mushroom body depends on the light environment; optic lobe size in flies reared in dark conditions is smaller than that of flies reared under full light (Barth et al, 1997b). Additionally, when D. melanogaster are reared in light environments, photoreceptor voltage responses to light contrast changes are amplified, favouring signalling performance (Wolfram and Juusola, 2004).…”
Section: Introductionmentioning
confidence: 99%